2019
DOI: 10.1177/1049909119836238
|View full text |Cite
|
Sign up to set email alerts
|

How to Talk About Attitudes Toward the End of Life: A Qualitative Study

Abstract: To individually plan end-of-life care, open communication about a person’s preferences and attitudes toward the end of life can facilitate dignity and quality of life in patients and relatives. To improve communication, structured guiding tools might be used as door openers. However, most tools focus on care preferences and decisions without assessing the person’s underlying attitudes in detail. This study aims to get insights into specific requirements and conditions for communication about the end of life in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 26 publications
1
41
2
2
Order By: Relevance
“…The DöBra cards were found to be useful to strengthen person-centered care provision and rapport both during and after EOL conversations. This is in contrast to a recent study by Groebe et al [44], in which some care staff considered EOL conversation tools to be counterintuitive to an individualized care approach. It may be that the physical format of the DöBra cards better allowed residents and/or relatives to be actively involved in directing the discussion than other conversation tools, as the cards they choose served as route markers for mapping the discussion, with as much -or little -commentary as residents and/or relatives wished.…”
Section: Discussioncontrasting
confidence: 96%
“…The DöBra cards were found to be useful to strengthen person-centered care provision and rapport both during and after EOL conversations. This is in contrast to a recent study by Groebe et al [44], in which some care staff considered EOL conversation tools to be counterintuitive to an individualized care approach. It may be that the physical format of the DöBra cards better allowed residents and/or relatives to be actively involved in directing the discussion than other conversation tools, as the cards they choose served as route markers for mapping the discussion, with as much -or little -commentary as residents and/or relatives wished.…”
Section: Discussioncontrasting
confidence: 96%
“…However, that might run contrary to the idea of ACP being held while persons are still able to communicate [ 22 ]. In addition, health care personnel have indicated that ACP close to dying is “too close and tense” and a peaceful atmosphere is needed [ 43 ]. Health care personnel may worry about causing patients harm by having untimely ACP discussions [ 44 ] and this can increase the uncertainties about when ACP is timely.…”
Section: Discussionmentioning
confidence: 99%
“…Updating available course offerings could also help to promote patient-centric considerations of preferences in terms of EOL care and dying. Training should address the need for early individualized approaches to EOL discussion, and their integration into existing care structures [ 23 ], which would ultimately promote favorable attitudes towards EOL practices among physicians [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…EOL care is an immature concept in Lebanon with little to no guidance provided to physicians in this regard. This could explain the attitude of Lebanese physicians seeing as insecurities among medical care staff often lead to delayed discussions with either patients or their relatives [ 23 ]. Shared decisions in the context of EOL also reflect societal, educational, cultural, and religious values in both patients and physicians.…”
Section: Discussionmentioning
confidence: 99%